Pathologies of vision : representations of deviant women and the cyborg body - Rheeder, Elle-Sandrah (Rhodes University, Faculty of Humanities, Department of Fine Art, 2015)
This thesis investigates the figure of the cyborg as conceptualised by Donna Haraway in The Cyborg Manifesto (1991). The figure of the cyborg, as a transgressive figure in the late twentieth century within socialist feminist discourse, is problematized with regard to its efficacy as a creature that challenges the constructed nature of gender and contests the boundary between human and machine through its ambiguous nature. Haraway's notions of the cyborg, which she bases partly on cyborg characters from Science Fiction literature, deny the ocularcentric traditions that have structured gender and the body. Similarly, Haraway does not engage adequately with the figure of the cyborg with regard to situating it historically. This thesis unpacks both the visual and the historical aspects that have structured the cyborg body. By engaging with these concepts, the cyborg emerges as a figure that is identified through visual signifiers of female deviance and pathology. By reading female deviance and pathology on the body of the nineteenth-century hysteric, similarities can be drawn between the hysteric and the cyborg. Through a reading of Alien (1979); Blade Runner (1982); and Star Trek: First Contact (1996) key cyborg texts of the late twentieth century, the figure of the cyborg, and its relation to the deviant pathologised female can be understood when read against the body of the hysteric and how it was visually coded and communicated
Keywords: Haraway, Donna Jeanne -- Criticism and interpretation; Deviant behavior in art; Cyborgs in art; Cyborgs in motion pictures; Women in art; Socialist feminism; Hysteria in literature; Hysteria -- History; Science fiction -- History and criticism; Visual communication in art